Rekrutmen, Seleksi dan Penempatan Syariah - Nun Tufa (Fakultas Ekonomi dan Bisnis Islam, 2019)
Abstract: The theme of the article is the business concept in Islamic economics. The purpose of writing is: to analyze recruitment, selection and placement based on Islamic law. This article is a study of literature. Islam is the most perfect religion. everything in Islam comes from God. God has revealed Al-Qur’an as a guideline for the Islamic ummah in carrying out every aspect of life. Hadiths are also used as a basis for Muslims. So is the case with the concept of Islamic human resource management. This paper explains how the Islamic Perspective regarding the process of recruitment, selection and placement of human resources. How is the process and implementation of recruitment, selection and placement in the Koran and Hadith which is the main reference for Muslims.